Experimental study and modeling of hygro-thermal behavior of polystyrene concrete and cement mortar. Application to a multilayered wall. (September 2016) - Chikhi, Ali; Belhamri, Azeddine; Glouannec, Patrick; Magueresse, Anthony
Abstract: Polystyrene concrete is used to reduce energy consumption in buildings and to recycle some waste. However, one records a lack of knowledge of its hygro-thermal characteristics. This study involves two aspects: the first aspect is to measure the thermo-physical properties of polystyrene concrete and cement mortar. The second aspect is to study the hygro-thermal behavior of these highly heterogeneous materials subjected to external excitations. Numerical and experimental approaches are used. For both approaches, the ambient conditions have a direct impact on the behavior of the walls. The studies are therefore conducted in varying climatic conditions on blocks placed in an experimental bench. In parallel to the experimental approach, a model representative of heat and mass transfer in materials: capillaro-porous media (composite concrete) and multiphasic media (coating of cement), is developed in order to predict hygro-thermal behavior of the wall. A numerical simulation of the hygro-thermal behavior is performed for a multilayered wall. Comparison is carried out when the discontinuity phenomenon, at the interface between two porous materials, is taken or not into account. The results show the advantage of replacing the ordinary concrete by a polystyrene concrete in constructions. They also show the importance of taking into account the discontinuity of the moisture content at the interface of materials that make up a multilayered wall. Highlights: Study on a building material with insulating character. Hygro-thermal behavior carried out on an instrumented blocks. Physical model validated by comparison of simulated and experimental results. Advantage of using polystyrene concrete compared to ordinary concrete. Numerical simulation carried out on a multilayer wall.